Fundamentals of tourism: What makes a person a potential tourist and a region a potential tourism destination? - LOHMANN, Martin; BEER, Henrike (Economics and Business Review, 2025)
The paper introduces a conceptual structural model to describe which central factors determine whether and where tourism takes place. It refers to five factors that are considered to be a prerequisite for tourism: assets, amenities (or facilities) and accessibility on the side of a potential destination, and ability and motivation to travel on the demand side. Empirical evidence is presented based on large sample population surveys in Germany of the strong influence of these five factors. Whether a person becomes a potential tourist or not depends strongly on ability and on the motivational intensity. In addition, the perception of assets, amenities, and accessibility (rated for 10 regions/countries) is essential for the selection of regions considered for the initial consideration set. Both findings support the structure and links used in the conceptual model. They thus emphasize the importance of these basic factors as fundamentals of tourism.